Gwarancje pochodzenia dla nowych nośników energii - Trela, Anna; Trupkiewicz , Marcin; Kosiński , Eryk (PRAWO i WIĘŹ, 2025)
In their study, the authors analyse the changes made to the Renewable Energy Sources Act with regard to guarantees of origin, in relation to the implementation of the RED II Directive. In the first part of the study, they describe the EU regulations introducing guarantees of origin as a document certifying to the end user that a given part or quantity of energy was produced from renewable sources. They then turn to the changes concerning the new energy carriers covered by guarantees of origin. In this regard, they analyse these carriers with reference to French and German regulations. They describe the procedure for obtaining guarantees of origin, pointing to the significant differences in the French system. The last part of the paper is devoted to the mutual recognition of guarantees of origin and Poland’s participation in the Association of Issuing Bodies.